Ответ(ы) на вопрос:
Гость
4cos²x-4sinx-1=0
cos²x=1-sin²x
4*(1-sin²x)-4sinx-1=0
-4sin²x-4sinx+3=0 |:(-1)
4sin²x+4sinx-3=0 тригонометрическое квадратное уравнение, замена переменной: sinx=t, t∈[-1;1]
4t²+4t-3=0
t₁=-1, t₂=1/2
обратная замена:
1. t=-1, sinx=-1. x=-π/2+2πn, n∈Z
2. t=1/2
sinx=1/2
[latex]x=(-1)[latex]x=(-1)^{n} * \frac{ \pi}{6}+ \pi n, n[/latex]∈Z
[latex]x=(-1) ^{n}* \frac{ \pi}{6} + \pi n, n[/latex]∈Z
ответ: [latex] x_{1}=- \frac{ \pi}{2}+2 \pi n, n[/latex]∈Z
[latex] x_{2}=(-1) ^{n}* \frac{ \pi}{6}+ \pi n, n[/latex]∈Z
Не нашли ответ?
Похожие вопросы